A study of chromium, nickel and cobalt hypersensitivity. - (:unkn) unknown (My University, 1992)
Hypersensitivity reactions to chromium, nickel and cobalt were investigated in the preclinical, fourth year and fifth year students of the Dentistry Faculty of Marmara University, Türkiye. A Standard patch test was performed. Four patches were applied to the shoulder blades of the students. Three of them contained small amounts of 0.5% potassium chromate, 5% nickel sulphate and 1% cobalt chloride respectively. The fourth (control) patch was of petroleum jelly. Questionnaires were used to determine sex and history of any previous allergy to jewelry. After 48 hours, the patches were removed and results assessed. For each base metal, no statistically significant difference was found in the incidence of hypersensitivity reaction between the groups. Nor was there a significant difference in response found between metals, for all of the students tested. Although women were found to have a higher rate of nickel hypersensitivity than men, no such sex difference was found chromium and cobalt. No significant relationship was found between a history of allergy to jewelry and chromium hypersensitivity, however there was a significant difference for nickel and cobalt hypersensitivity. In confirmation of our tests, significant relationships were found between previous allergy histories and the respective patch test results.